2021
DOI: 10.21203/rs.3.rs-1032996/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of Neoadjuvant Therapy for Neuroendocrine Cervical Tumors

Abstract: Purpose. This study aimed to assess the cost-effectiveness of neoadjuvant therapy in combination with surgery and adjuvant therapy compared with either surgery alone or surgery plus adjuvant therapy for the treatment of neuroendocrine cervical tumors (NETs). Materials and methods. A single-institution retrospective analysis of 107 patients with NETs was performed based on the new International Federation of Gynecology and Obstetrics (FIGO 2018) staging system. We divided the patients who underwent radical surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…After layer-by-layer screening according to the inclusion and exclusion criteria, a final set of 14 articles was included, including 8 SR or meta-analysis [15][16][17][18][19][20][21][22] and 6 pharmacoeconomic studies. [25][26][27][28][29][30] No HTA report was retrieved. The literature screening process and results are provided in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After layer-by-layer screening according to the inclusion and exclusion criteria, a final set of 14 articles was included, including 8 SR or meta-analysis [15][16][17][18][19][20][21][22] and 6 pharmacoeconomic studies. [25][26][27][28][29][30] No HTA report was retrieved. The literature screening process and results are provided in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The research findings from Men et al [28] and He et al [29] both support that, compared to conventional treatment alone, the incremental cost-effectiveness ratio (△C/△E) is lower with the combination of Cerebrolysin injection. The study by Lin et al [25] suggested that in terms of significant efficacy and reasonable cost, Cerebrolysin was the preferred option compared with citicoline. Furthermore, Table 4 Quality evaluation of included pharmacoeconomic studies.…”
Section: Economy Of Therapeutic Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, at each stage along the care pathway, cost-efficiency can be maximised through a comprehensive understanding of the patient population, health system capacity and resources, as well as the most appropriate diagnostic tools, treatments and supportive care interventions. There is some evidence of the cost-effectiveness of specific treatments for NENs, 94,95,[131][132][133][134][135][136][137] and cost-efficiency of care pathways for other conditions has been demonstrated. [13][14][15][16][17][18] It is important to note, however, that there is currently insufficient evidence on the costeffectiveness of many types of NEN management.…”
Section: Discussionmentioning
confidence: 99%